Topographic Effects on the Seismic Response of Trapezoidal Canyons Subjected to Obliquely Incident SV Waves - Hui Shen; Yaqun Liu; Haibo Li; Bo Liu (Shock and Vibration)
The topography and the incident angle of seismic waves both have considerable effects on the seismic ground motions of canyons in a half-space. In this paper, the theory of wavefield decomposition and the artificial boundary is used to develop a method for inputting obliquely incident SV waves. Formulas for the equivalent nodal forces applied to the truncated boundary are derived and implemented in the finite element method. The validity of the proposed method is verified by a test case. A parametric study is then performed to investigate the influence of canyon geometry and incident angle of SV waves on the seismic response of trapezoidal canyons. The numerical results indicate that the canyon inclination has a more significant effect on the ground motion amplification than its height and width. The amplification effects are strongly related to the canyon inclination and the incident angle of SV waves. Additionally, the dominant frequency corresponding to the acceleration of the canyon crests is not sensitive to the incident angle of SV waves.